Implementation of Urban Village Fund Allocation Policy in Airmadidi District - Lumempouw, Pretty Veronika; Pangkey, Itje; Mamonto, Fitri H. (Technium Social Sciences Journal, 2025)
This study aims to analyze the implementation of the urban village fund allocation policy in Airmadidi District, North Minahasa Regency . Urban village funds are a form of budget support from the central and regional governments aimed at strengthening community development and empowerment in urban areas. Although regulatively the allocation of funds has been determined, the implementation of policies in the field still faces various challenges. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation studies. Research informants consisted of urban village officials, district officials, community leaders, and members of urban village community institutions. This research uses the Edward III policy implementation model which includes four variables: communication, resources, disposition (executor attitude), and bureaucratic structure. The results showed that the implementation of the urban village fund allocation policy in Airmadidi District has not been running optimally. The main obstacles lie in the lack of coordination between parties, limited human and budgetary resources, and low community participation in the planning and monitoring process. In addition, not all urban village have consistently applied the principle of transparency in budget management. The conclusion of this study is that the successful implementation of the urban village fund allocation policy depends on the clarity of policy communication, readiness of local resources, and active community involvement. Institutional capacity building and a more structured evaluation mechanism are needed for this policy to run effectively and sustainably.